2019
DOI: 10.3145/epi.2019.may.12
|View full text |Cite
|
Sign up to set email alerts
|

Uso del móvil y las redes sociales como canales de verificación de fake news. El caso de Maldita.es

Abstract: Uso del móvil y las redes sociales como canales de verificación de fake news. El caso de Maldita.es Using mobile devices and social networks as checking channels of fake news. The case of Maldita.es

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 10 publications
0
14
0
7
Order By: Relevance
“…The sample of fake news analysed was obtained from the Maldita.es website, a project that is part of the International Fact-Checking Network initiative, which has been collecting fake news since 2017 ( Bernal-Triviño and Clares-Gavilán, 2019 ). The methodology, on the basis of which it is established whether a news item is considered false, is described on the website ( Maldita.es, 2018 ); it focuses mainly on the verification process while omitting details regarding the news selection process.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sample of fake news analysed was obtained from the Maldita.es website, a project that is part of the International Fact-Checking Network initiative, which has been collecting fake news since 2017 ( Bernal-Triviño and Clares-Gavilán, 2019 ). The methodology, on the basis of which it is established whether a news item is considered false, is described on the website ( Maldita.es, 2018 ); it focuses mainly on the verification process while omitting details regarding the news selection process.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, health news was classified under science. A previous analysis of fake news collected from Maldita.es revealed that, out of 568 news items, most had politics as the main theme (35%), whilst the rest were distributed among people (15%), immigration and racism (12%), gender (10%) and science (9%) ( Bernal-Triviño and Clares-Gavilán, 2019 ). I decided to remove ‘people’ as a category because many fake news pieces specifically attack people in the world of politics and thus have a political intention.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RLCS,Revista Latina de Comunicación Social ,79,[51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68] [Investigación] DOI: 10.4185/RLCS-2021-1512| ISSN 1138-5820 | Año 2021 La presencia de noticias falsas es una de las cuestiones que amenaza seriamente la credibilidad en las redes sociales (Blanco Alfonso et al, 2019). Se ha demostrado que las noticias falsas se difunden con más facilidad, rapidez y alcance que el resto de las informaciones y su principal medio de propagación son las redes sociales (Bernal-Triviño y Clares-Gavilán, 2019;Papadopoulos et al, 2016;Vosoughi et al, 2018). Una alta incidencia de usuarios reconocen haber tenido contacto con noticias falsas a través de gente que no conocen (42%), procedente de políticos (43%) o de organizaciones de noticias (36%) según informan Nielsen et al, (2020).…”
Section: Introductionunclassified
“…Media organizations have introduced fact-checking. These measures are of interest to the scientific community, with studies documenting the verification initiatives implemented at both the international level [8] and the national level, such as B de Bulo [9] or Maldita.es [10]. The similarities and discrepancies between academic and professional discourse around fact-checking have also been analysed [11], as has the role journalistic deontology plays as a tool in the fight against fake information [12].…”
Section: Introductionmentioning
confidence: 99%